Analisis Pesan Dakwah pada Film “Cinta Subuh” Karya Ali Farighi (Semiotika Roland Barthes) Bagi Siswa Kelas X MAS Amaliyah Sunggal - Audina, Marsha; Hasibuan, Abdullah (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This study aims to analyze the da'wah messages in the film "Cinta Subuh" directed by Ali Farighi. Da'wah themes are commonly found in the world of films, prompting the author to conduct a research on the da'wah messages depicted in the film using Roland Barthes' semiotic analysis, specifically focusing on aqidah (faith), morals, and sharia (Islamic law) aspects. The findings of this research contribute to a deeper understanding of works related to da'wah and serve as a valuable reference for future writers. Moreover, it is expected to inspire da'wah practitioners to harness the potential of films as a medium for delivering impactful messages and to provide a positive viewing experience for all audiences who appreciate this film. This research employs a qualitative method approach, utilizing Roland Barthes' semiotic analysis. Data collection for the film analysis involves recording, listening, taking notes, and categorizing relevant information. The study's outcomes reveal the existence of da'wah messages encompassing aqidah, morals, and sharia themes within the film "Cinta Subuh."